2021
DOI: 10.1016/j.heliyon.2021.e05975
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the prevalence, density, and risk factors associated with malaria transmission in urban communities of Ibadan, Southwestern Nigeria

Abstract: Background: Malaria is a severe global public health challenge that causes significant morbidity and mortality worldwide, particularly in sub-Saharan Africa. This study was designed to determine the prevalence, parasite density, and risk factors associated with malaria infection transmission among residents of two urban communities of Ibadan, southwestern Nigeria. Materials and methods: A cross-sectional hospital-based study was carried out on 300 participants. Blood samples were obtained. Thick and thin blood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
64
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 29 publications
17
64
3
Order By: Relevance
“…Furthermore, our findings revealed that P. falciparum was the only Plasmodium species encountered in this study. This is similar to the report of studies conducted in Ekiti and Ibadan, southwestern Nigeria 53 , 54 and other malaria endemic settings. 32 , 55 , 56 This is due to the fact that P. falciparum is a dominant Plasmodium species in Nigeria and Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our findings revealed that P. falciparum was the only Plasmodium species encountered in this study. This is similar to the report of studies conducted in Ekiti and Ibadan, southwestern Nigeria 53 , 54 and other malaria endemic settings. 32 , 55 , 56 This is due to the fact that P. falciparum is a dominant Plasmodium species in Nigeria and Africa.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research confirmed that age, sex, marital status of the respondent [ 5 ], proximity to mosquito breeding sites such as stagnant water [ 7 ], temperature, humidity, precipitation, education, occupation, and income are the main risk factors that favor the transmission of malaria [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The onset of severe malaria and fatal disease, not totally restricted to Plasmodium falciparum infections, can lead to mortality. The important health complications of malaria that can lead to mortality include celebral malaria, pulmonary edema, acute renal failure, severe anemia, bleeding, acidosis, and hypoglycemia ( 2 , 3 ). Reports indicate that 216 million cases of malaria occurred worldwide resulting in global mortality of 445,000 in 2016.…”
Section: Introductionmentioning
confidence: 99%